Virtual and Augmented Realms: The Evolution of Video Games with VR and AR Technology - Ishika Tiwari; Dheeraj Solankar; Dr. Rajeshree Khande (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
The incorporation of virtual reality (VR) and augmented reality (AR) technologies into video games has transformed the industry. After the introduction of mobile phones and portable devices, the gaming industry saw a transformation in these new market platforms. Moreover, in recent years, another aspect, among many others, that has contributed to the enhancement of gamers' experiences is VR and AR. The growing popularity of VR and AR technologies, as well as developments in the technology, have resulted in a new era of gaming experiences that allow gamers to fully immerse themselves in digital settings. This research study looks at how video games have evolved with VR and AR technologies, covering the development of VR and AR devices and how they have affected game design [3][4]. Moreover, the study addresses the possible future of VR and AR in gaming, as well as their influence on the industry. We employed secondary data, such as surveys, and online data collection from numerous gamers to create this thorough study as we were dealing with such extensive subject. This research paper provides a comprehensive overview of the current state of VR and AR in video games and highlights the opportunities and challenges that lie ahead. Technology in the AR/VR space has been around for a very long time. It has changed to meet the demands of the users, offering a variety of gaming options and settings for everyone to enjoy and spend time in while embracing technological advancements that are enabling them to experience various situations. This study's conclusion is that AR/VR gaming has advanced significantly, and its future depends on a variety of aspects, including how it will impact learning and healthcare. As a result of the general public's interest in this industry and the development of numerous novel inventions to keep players engaged and craving more, VR hardware prices are lowering relatively.